Comparison of the 3D triple-scan protocol and the impression replica technique for 3-unit tooth-supported fixed dental prostheses. Issue 1 (20th December 2019) - Svanborg, Per; Andersson, Miranda; Reinedahl, Therese; Alstad, Torgny
Abstract: Objective: The aim of this study was to compare the fit measurements from the 3 D triple-scan protocol and the impression replica technique, by measuring the fit of three-unit tooth-supported fixed dental prostheses. Materials and methods: The results from an earlier study using the triple-scan protocol were compared to results from the impression replica technique for absolute marginal gap, cervical area gap and internal gap. Results: There were no differences for cervical area gap or internal gap, but for absolute marginal gap the impression replica technique obtained significantly smaller fit values. Conclusion: The impression replica technique and the triple-scan protocol may both be used to measure the fit of tooth-supported restorations. However, the scanner used for the triple-scan protocol must be able to obtain scan points at the outermost edge of the restorations when used for absolute marginal gap.